Development of metal-doped ZnO catalysts for photocatalytic degradation of caffeine (Research, Society and Development, 2022)
Currently, conventional wastewater treatment processes are unable to remove certain pollutants, such as contaminants of emerging concern, considered an environmental problem. In this way, there is a growing search for new alternatives to effluent treatments, in order to remove these pollutants, including caffeine, which is present in different foods, being found in water for human consumption. Heterogeneous photocatalysis, an advanced oxidation process, is an efficient alternative for the removal of these substances. In this context, the present work aimed to develop metal-doped ZnO catalysts and study their performance in the photocatalytic degradation reaction of caffeine. The addition of metals to the catalyst improves its properties, especially its absorption capacity in the visible region. First, the commercial ZnO catalyst was tested in the photocatalytic removal of caffeine under UV radiation, being determined, through an experimental design, the best experimental conditions, in which 96.88% of caffeine degradation was reached. Subsequently, commercial ZnO was doped with silver (Ag), nickel (Ni) and copper (Cu), and these synthesized catalysts were characterized by means of specific surface area analysis, scanning electron microscopy, infrared spectroscopy and fluorescence of X ray. Finally, the performance of the synthesized catalysts was evaluated in the photocatalytic degradation reaction of caffeine, under the best experimental conditions under visible radiation. The catalyst with the addition of 8% of Ag by weight, was the one that obtained the best performance in the photocatalytic removal of caffeine, reaching a degradation of 87.47%.